PENGARUH PUPUK NPK DAN URINE KELINCI TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicumL.) - Viqri, Muhammad; Deviona, Deviona; Isnaini, Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Shallots (Allium ascalonicum L.) is one of horticultural commodities that have been intensively cultivated by farmers for a long time. The need for shallots continues to increase along with the increase in population. Currently the productivity of shallots in Riau Province is still low. This study aims to see the effect of the interaction of fertilizer application NPK and Organik Liquid Fertilizer rabbit urine and get the best dose on the growth and production of shallots. This research has been carried out at the Technical Implementation Unit (UPT) of the University of Riau, Bina Widya Campus KM 12.5, Simpang Baru Village, Tampan District, Pekanbaru. The study started from July 2019 to October 2019. The method used in this study was a factorial randomized block design (RAK) consisting of two factors, namely, the first factor was fertilizer NPK P1: 100 kg.ha-1(0,25 gram), P2 : 200 kg.ha-1(0,5 gram) dan P3 : 300 kg.ha-1(0,75 gram). While the second factor is rabbit urine liquid organic fertilizer U1 :100 ml.l-1, U2 :150 ml.l-1, U3 :200 ml.l-1 and U4 :250 ml.l-1. Observations made included plant height (cm), number of leaves (strands), number of tubers per clump, tuber diameter, weight of fresh tubers and weight of tubers fit for storage. The data obtained were analyzed by means of variance and the results of the analysis were further tested with the Duncan's test at the 5% level. Keyword(s): Shallots, NPK fertilizer, Organik Liquid Fertilizer